2004
DOI: 10.1099/vir.0.80283-0
|View full text |Cite
|
Sign up to set email alerts
|

Histidine 39 in the dengue virus type 2 M protein has an important role in virus assembly

Abstract: The mature flavivirus particle comprises a nucleocapsid core surrounded by a lipid bilayer containing the membrane (M) (derived from the precursor prM) and envelope (E) proteins. The formation of intracellular prM/E heterodimers occurs rapidly after translation and is believed to be important for the assembly and secretion of immature virus particles. In this study, the role of the His residue at position 39 in the M protein (M39) of dengue virus type 2 (DENV-2) in the virus life cycle was investigated. Mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 60 publications
3
23
1
Order By: Relevance
“…Each of the remaining upper fractions contained 6.5% or less of the total E signal, with a small peak in fractions 10 to 11. Consistent with the findings of previous reports (20,34), the prM proteins in the upper sucrose fractions were enriched with the faster-migrating species, whereas those in the lower fractions contained the faster-and slower-migrating species in approximately equal amounts (Fig. 3A).…”
Section: Vol 82 2008 Modulation Of Dengue Virus Prm Cleavage and Insupporting
confidence: 81%
See 2 more Smart Citations
“…Each of the remaining upper fractions contained 6.5% or less of the total E signal, with a small peak in fractions 10 to 11. Consistent with the findings of previous reports (20,34), the prM proteins in the upper sucrose fractions were enriched with the faster-migrating species, whereas those in the lower fractions contained the faster-and slower-migrating species in approximately equal amounts (Fig. 3A).…”
Section: Vol 82 2008 Modulation Of Dengue Virus Prm Cleavage and Insupporting
confidence: 81%
“…Therefore, the majority of extracellular viral particles generated by the parent virus were rapidly sedimenting virions. The predominance of virions observed for the 16681Nde(ϩ)-infected C6/36 cultures was in accordance with previous results obtained from dengue virus-infected C6/36 and Vero cells (24,34). A similar distribution of particles was observed with the E199A and S206A mutants, in which prM cleavage was minimally affected (Fig.…”
Section: Vol 82 2008 Modulation Of Dengue Virus Prm Cleavage and Insupporting
confidence: 80%
See 1 more Smart Citation
“…However, little is known about the role of M protein including the MH domain (positions 112-131) in the replication cycle of DENV. Previously, Pryor et al (44) reported that a histidine residue at position 130 is important for assembly of DENV2 virions; we reported that proline substitutions of residues in the MH domain (positions 120, 123, and 127) of DENV prM protein greatly affect the entry and assembly of VLPs and virions, suggesting the importance of the C terminus of MH domain (45). Sequence analysis of the MH domain revealed nine residues highly conserved among different strains of four DENV serotypes (see Fig.…”
Section: The Envelope and Precursor Membrane (Prm) Proteins Of Denguementioning
confidence: 99%
“…The perimembrane and transmembrane helices serve to anchor the M protein to the membrane. In the case of DV and JEV, the perimembrane helix region was shown to be involved in virus assembly (30)(31)(32)(33) and entry (31,32). Subsequent mutagenesis analysis of the M protein proved the importance of an interactive network between E and M in those processes (16,34,35).…”
mentioning
confidence: 99%